Digital maturity of business: Technological gap and limitations of digital transformation - I. S. Prokhorova; P. M. Gureev (Вестник университета)
Digital maturity of business is the object of the study. The subject of research is the process of systemic digital transformation of business. Research methods include indicative method and the method of system analysis. The premise of the study is to identify the unsystematic digitalization of business in industry as one of the significant problems of achieving digital maturity in the Strategy for Digital Transformation of Manufacturing Industries in the Russian Federation. The purpose of the study is to identify the reasons for the unsystematic processes of business digitalization to achieve “digital maturity”. To achieve this goal, technological trends in the global systemic digital business transformation were analyzed and monitoring of the compliance of digital business transformation processes in Russia with the identified characteristics of global systemic business digitalization was carried out. The study showed that in the Russian business sector there is a technological gap with the global processes of digital business transformation. As a result of the study, it was found that the main reasons for the unsystematic processes of digitalization of Russian business are the low quality of business digitalization with high digital activity and low technological capabilities for implementing Industry 4.0 technologies due to the limited use of the Internet mobile network in business, business cybersecurity tools, Internet communications and cloud services. The increment of knowledge consists in determining the technological principle of digital business transformation at the global level – this is a mobile device operating on the principles of machine-to-machine interaction M2M with big data IoT (Internet of things) based on 5G speeds and Wi-Fi 6 communication standards, as well as identifying a system of indicators for monitoring the technological basis for managing the “digital maturity” of a business.